Burundi: Challenges and Conflicts - Finnegan, Dorothy (International Higher Education, 2009)
Burundi's educational system reflects not only its colonial and war-torn past but also its precarious and meager national fiscal situation.The ethnic wars, followed by continuing tension and political power struggles, coupled reportedly with a lack of governmental vision, have inhibited the significant gains realized by Burundi after independence. Regardless of the shortcomings of the resources at the universities, administrators are actively seeking assistance to modernize their infrastructure and curricular offerings.